Adaptive protection scheme for microgrids - Vaithilingam, C; Jain, Himani; Ojha, Medha; Singh, Meghna; Vijay Joseph Samuel, J (International Journal of Engineering and Technology, 2018)
Micro grids are gaining attention to become an integral part of traditional power system, due to their numerous technical benefits and their ability to improve power system reliability.Voltage regulation, reduction in Transmission and distribution losses, reduction in the need for transmission capacity addition etc are the few technical benefits of micrgrids with renewable energy sources. However, a protection scheme that suits a conventional power system will require a major revamp if micro grids need to be interfaced. The power generations of each renewable source, mode of operation of microgrids are the few important factors to be considered to fix the relay settings. The conventional over current protection scheme faces selectivity and sensitivity issues during the grid faults and the microgrid faults, since the fault current level is different in both the cases. Hence, electro mechanical and static relays may not be suitable for the protection of power systems with microgrids. The processor based relays with augmented intelligence, that is, a relaying scheme which can act according to the operating condition need to be developed. This paper proposes an adaptive protection scheme for power systems with microgrids. The proposed method in this paper is tested with a hardware prototype resembles the actual microgrid setup.